2014
DOI: 10.1016/j.neuropsychologia.2014.08.020
|View full text |Cite
|
Sign up to set email alerts
|

The steady-state visual evoked potential reveals neural correlates of the items encoded into visual working memory

Abstract: Visual working memory (VWM) capacity limitations are estimated to be ~4 items. Yet, it remains unclear why certain items from a given memory array may be successfully retrieved from VWM and others are lost. Existing measures of the neural correlates of VWM cannot address this question because they measure the aggregate processing of the entire stimulus array rather than neural signatures of individual items. Moreover, this cumulative processing is usually measured during the delay period, thereby reflecting th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 66 publications
(78 reference statements)
2
19
0
Order By: Relevance
“…In closing, by examining the neural signals generated by frequency tags for each to-be-encoded stimulus, we build upon our previous findings [45] that highlighted the role of errors at encoding as a contributing factor of VWM capacity. By focusing on neural set-size effects for correct trials, the current study revealed that like VWM as a whole, encoding-related neural resources are likely capacity-limited.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In closing, by examining the neural signals generated by frequency tags for each to-be-encoded stimulus, we build upon our previous findings [45] that highlighted the role of errors at encoding as a contributing factor of VWM capacity. By focusing on neural set-size effects for correct trials, the current study revealed that like VWM as a whole, encoding-related neural resources are likely capacity-limited.…”
Section: Discussionmentioning
confidence: 94%
“…Frequency-tagging entails rapid and periodic stimulus presentation, inducing corresponding rapid-periodic responses in the simultaneously recorded EEG [44]. We reported that the frequency-tag amplitudes during encoding were significantly larger for successfully remembered items compared to subsequently forgotten items [45]. The frequency-tags of unprobed items were also greater on correct trials.…”
Section: Introductionmentioning
confidence: 99%
“…Effective attention measurement can help to understand the mechanisms of attention. As an attention tag, SSVEP has been widely adopted in feature attention [4,5], working memory [6,7], binocular competition [8,9], facial processing [10,11], biological motion [12,13], and so on. Usually, SSVEP includes fundamental frequency components to examine low-level visual processing, harmonic frequency components to characterize high-level cognitive processing, and intermodulation frequency components to measure the interaction of the nervous system [14].…”
Section: Introductionmentioning
confidence: 99%
“…Norcia et al, 2015 for review), working memory (e.g. Perlstein et al, 2003;Peterson et al, 2014), or face processing (see Rossion, 2014 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…In an orientation discrimination task, SSVEP activity produced a tuned response that peaked at the angle of the stimulus (Garcia, Srinivasan, & Serences, 2013). In a visual working memory task, SSVEP amplitudes were larger for stimuli that were later remembered than for items that were subsequently forgotten (Peterson et al, 2014, see also Perlstein et al, 2003). Finally, it is well established that attention modulates SSVEP amplitude with attended items systematically exhibiting greater amplitudes compared to unattended items (e.g.…”
Section: Introductionmentioning
confidence: 99%